Updates on information about free-living marine nematodes in Brazil: new records and comments on problems in taxonomic studies - Venekey, Virág (Zootaxa, 2017)
New records of nematode species in Brazil, which appeared after or were not mentioned in the last review, are shown in this paper. All environments were considered, including the continental margin. In addition, all studies on marine nematodes in Brazil, including grey literature, ecological papers and book chapters, are listed. Furthermore, information on genera/species richness, dominant genera, and densities is also presented. A total of 11 orders, 72 families, 372 genera, and 450 species of nematodes were recorded in Brazilian marine environments by April 2017. Following problems are discussed: taxonomic lists available only in grey literature, use of outdated identification keys (leading to incorrect identifications), and identifications mostly to putative species or to the genus level.